Fungi Present on Pinus taeda Needles in Early Stages of Decomposition in the Field - Ghizelini, Angela Michelato (2011)
Knowing of the dependence between local area productivity, nutrient cycling and litter decomposition process, the knowledge of the mycobiota responsible for decomposition is the right way to obtain answers about forest´s productivity and nutrient´s demand. This study determined the fungal diversity during litter decomposition of needle of Pinus taeda in an experimental plantation with four years old, located at Três Barras, SC, Brazil. Senescent needles were collected from trees in november/2003 and putted in selective bags for microorganisms, which were left over the forest litter. The first sample was taken to the laboratory and the remaining ones were kept in situ so that the needles continue their natural decomposition process and were collected every three months. The collected needles were submitted at 20 successive washings. Fragments were taken off and inserted in Petri dishes containing malt extract agar 2% and were incubated at enviromental conditions. During fungi succession, 13 genera were identified: Acremonium sp., Alternaria sp., Cladosporium sp., Colletotrichum sp., Epicoccum sp., Fusarium sp., Gliocladium sp., Mucor sp., Penicillium sp., Pestalotia sp., Rhizoctonia sp., Trichoderma sp. and Verticillium sp. The most significant fungi were Trichoderma sp., Fusarium sp. and Verticillium sp. It was considered that the present fungal biodiversity is enough to start needle decomposition, by presence of cellulolitic fungi.